Анализ «спасенной» плазмиды из трансгенного тутового шелкопряда - Николаев, Л.И.; Чкоиия, Т.Т.; Эристави-Кафиани, К.А.; Тарантул, В.З. (Биополимеры и клетка, 1992)
С помощью оригинальной методики микроинъекций ДНК в грену тутового шелкопряда получены трансгенные особи. Из суммарной ДНК F₂-потомков этих животных "спасена" плазмида (рг8а), которая отличалась по своей структуре от переносимой плазмиды pL5LTR и наследовалась внехромосомно. В составе плазмиды pr8а Обнаружены повторяющиеся последовательности ДНК тутового шелкопряда, которые эволюционноконсервативны. За допомогою оригінальної методики мікроін'єкцій ДНК до грени тутового шовкопряду отримано трансгенні особини. З сумарної ДНК F₂-нащадків цих тварин «врятовано» плазміду (рг8а), котра відрізнялася за своєю структурою від перенесеної плазміди pl.5LTR і спадкувалася позахромосомно. У складі плазміду pr8а виявлено повторювані послідовності ДНК тутового шовкопряду, які є еволюційно консервативними. With the aid of microinjection of plasmid pPrC-LTRl,5. harboring 1.5 DNA copies of Rous sarcoma virus (RSV) long terminal repeats (LTRs) in vector pBR322, transgenic silkworms (Bombyx mori L.) were obtained. The transgene was transmitted in three, obtained up to now, generation. Most of the exogenous DNA is not integrated into the genome and persist as an extrachromosomal element which was subject to rearrangements. Plasmids have been rescued that carry the part of injected DNA and also fragments of the silkworm cellular DNA. In one of the rescued plasmids a sequence was found that is a member of a family of evolutionally concerved repeated sequences.